Piezoelectric film laminate and method for manufacturing same
Patent Information
- Application Number
- JP2021015022
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-02
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-02-02
AI Technical Summary
【0007】 また、請求項4に記載の発明によれば、 圧電膜積層体の製造方法は、 下地材(11)を用意すること(S1)と、 下地材の表面上にScAlN膜(12)を成膜すること(S2)と、 アニールにより、ScAlN膜に対して不対電子密度を調整すること(S3)と、を含み、 不対電子密度を調整することにおいては、ScAlN膜を成膜するときの成膜温度よりも高いアニール温度で、ScAlN膜を加熱することで、ScAlN膜の不対電子密度を8.0×1018(個/cm3)以上、1.1×1019(個/cm3)以下とする。
Smart Images

Figure 0007639372000002 
Figure 0007639372000003 
Figure 0007639372000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a piezoelectric film laminate in which a piezoelectric film and a base material are laminated, and a method for manufacturing the same. [Background technology]
[0002] Patent Document 1 discloses a piezoelectric film laminate including a base material and a piezoelectric film, an ScAlN film. The ScAlN film has a characteristic of being more piezoelectric than an AlN film. For this reason, it is expected that the piezoelectric film laminate including the ScAlN film will be applied to various devices. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-1456677 A Summary of the Invention [Problem to be solved by the invention]
[0004] When applying a piezoelectric film laminate including an ScAlN film to various devices, it is desirable for the ScAlN film to have a low tan δ. Tan δ is one of the electrical properties called the dielectric tangent, and is also called the loss factor. More specifically, tan δ is a value that indicates the degree to which a part of the electrical energy is lost as heat in a dielectric when an AC electric field is applied to the dielectric.
[0005] In view of the above, an object of the present invention is to provide a piezoelectric film laminate including an ScAlN film with a low tan δ, and a method for manufacturing the same. [Means for solving the problem]
[0006] In order to achieve the above object, according to the invention described in claim 1, The piezoelectric film laminate is Base materials (11, 25, 27, 32, 34, 41, 54) and A ScAlN film (12, 24, 31, 42, 53) formed on a surface of a base material, The unpaired electron density of the ScAlN film is 8.0×10 18 (pcs / cm 3 )The end, 1.1×10 19 (pcs / cm 3 ) or less.
[0007] In addition, claims 4 According to the invention described in The method for producing the piezoelectric film laminate includes the steps of: Preparing a base material (11) (S1); forming a ScAlN film (12) on the surface of the base material (S2); By annealing, (S3) adjusting the unpaired electron density for the ScAlN film; In adjusting the density of unpaired electrons, the ScAlN film is heated at an annealing temperature higher than the deposition temperature when the ScAlN film is formed, thereby adjusting the density of unpaired electrons in the ScAlN film. 8.0×10 18 (pcs / cm 3 ) End , 1.1×10 19 (pcs / cm 3 ) below.
[0008] Here, the present inventors determined that the dominant factor of tan δ of the ScAlN film is the density of unpaired electrons, and that the density of unpaired electrons in the ScAlN film is 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 ) or less, it was found that the tan δ of the ScAlN film could be kept low.
[0009] Therefore, according to the invention as set forth in claim 1, it is possible to provide a piezoelectric film laminate including an ScAlN film with a low tan δ. 4 According to the invention described in the above, it is possible to provide a method for manufacturing a piezoelectric film laminate including an ScAlN film with a low tan δ.
[0010] The reference symbols in parentheses attached to each component indicate an example of the correspondence between the component and specific components described in the embodiments described below. [Brief description of the drawings]
[0011] [Figure 1] 1 is a cross-sectional view of a piezoelectric film laminate in a first embodiment. [Diagram 2] 4 is a flowchart showing a manufacturing procedure of the piezoelectric film laminate in the first embodiment. [Diagram 3] FIG. 1 is a graph showing the relationship between unpaired electron density and tan δ for a number of piezoelectric film laminates manufactured by the present inventor. [Figure 4] FIG. 13 is a diagram showing the relationship between the annealing temperature and tan δ for a number of piezoelectric film laminates manufactured by the present inventor. [Diagram 5] FIG. 11 is a cross-sectional view of a microphone in a second embodiment. [Figure 6] FIG. 11 is a perspective view of a BAW resonator according to a third embodiment. [Figure 7] FIG. 13 is a perspective view of a SAW device in a fourth embodiment. [Figure 8] FIG. 13 is a cross-sectional view of a MEMS resonator according to a fifth embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present invention will be described with reference to the drawings. In the following embodiments, parts that are the same or equivalent to each other will be denoted by the same reference numerals.
[0013] (First embodiment) 1, a piezoelectric film laminate 10 of this embodiment includes a base material 11 and a ScAlN film 12. The base material 11 and the ScAlN film 12 are laminated.
[0014] The base material 11 is used as a base for the ScAlN film 12. The base material 11 is in contact with the ScAlN film 12 and supports the ScAlN film 12. An electrode material or a material other than an electrode material is used as a material constituting the base material 11. Examples of the electrode material include a semiconductor material, a metal material, and a conductive ceramic material.
[0015] An example of a semiconductor material constituting the base material 11 is Si. That is, a Si substrate can be used as the base material 11. When a Si substrate is used, the resistivity of the Si substrate is set to an arbitrary value depending on the application.
[0016] The metal material constituting the base material 11 is preferably one whose crystallinity and the like do not change during annealing in the manufacture of the piezoelectric film laminate 10 described below, and is preferably one with a high melting point. In addition, the metal material constituting the base material 11 is preferably one that has a long history of use in semiconductor processes including MEMS. Metal materials that satisfy these requirements include Mo, Ti, Pt, Ru, and the like.
[0017] Titanium compounds such as TiN can be cited as conductive ceramic materials that form the base material 11. TiN is often used as an electrode material in semiconductor processes.
[0018] The base material 11 is not limited to a single member, and may be made of a plurality of members. That is, the ScAlN film 12 may be formed on the surface of each of the plurality of members serving as the base material 11.
[0019] The ScAlN film 12 is a piezoelectric film made of ScAlN (that is, scandium-containing aluminum nitride). The ScAlN film 12 is formed on the surface of the base material 11.
[0020] The Sc concentration of the ScAlN film 12 may be any concentration greater than 0 atomic % and equal to or less than 45 atomic %. The Sc concentration is the ratio of the number of Sc atoms to the total number of Sc atoms and Al atoms, which is 100 atomic %. The atomic % refers to hundreds of atomic percentages. The Sc concentration is measured by RBS. RBS is an abbreviation for Rutherford Backscattering Spectrometry. The Sc concentration shown in this specification is a value measured using the following apparatus under the following measurement conditions.
[0021] Device name: National Electrostatics Corporation Pelletron 3SDH Measurement conditions RBS measurements Incident ions: 4He++ Incident energy: 2300keV Incident angle: 0deg Scattering angle: 160deg Specimen current: 13nA Beam diameter: 2mmφ In-plane rotation: None Irradiance: 70μC
[0022] The unpaired electron density of the ScAlN film 12 is 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 ) or less. The unpaired electron density is also called dangling bond density or electron spin density. The unpaired electron density is measured by electron spin resonance. The unpaired electron density value of the ScAlN film 12 shown in this specification is a value measured using the following ESR device under the following measurement conditions. ESR is an abbreviation for Electron Spin Resonance.
[0023] Device name: Elexsys E580 (BRUKER) Accessory equipment: ER036TM Gaussmeter (BRUKER) Measurement conditions Measurement temperature: 20K Central magnetic field: around 3362 G Magnetic field sweep range: 1000 G Modulation: 100kHz, 5G Microwave: 9.42 GHz, 0.01 mW Sweep time: 167.77 s x 4 times Time constant: 327.68 ms Number of data points: 2048 points Cavity: super-high-Q
[0024] For example, an upper electrode may be present on the upper surface of the ScAlN film 12, which is the target of electron spin density measurement. Also, a lower electrode may be present on the lower surface of the ScAlN film 12, which is the target of electron spin density measurement, and a substrate may be present on the lower surface of the lower electrode. In these cases, it is difficult to measure the electron spin density of the ScAlN film in the presence of the upper or lower electrode.
[0025] Therefore, if an upper electrode is present, it is removed by etching or the like. This makes it possible to measure the electron spin density. If a lower electrode and substrate are present below the ScAlN film, the substrate below the ScAlN film is removed by machining or etching while the upper surface of the ScAlN film is fixed to another substrate. Furthermore, the lower electrode is removed by etching. This makes it possible to measure the electron spin density.
[0026] Next, a method for manufacturing the piezoelectric film laminate 10 of this embodiment will be described. As shown in Fig. 2, the method for manufacturing the piezoelectric film laminate 10 includes a base material preparation step S1, a film formation step S2, and an annealing step S3.
[0027] In the base material preparation step S1, a base material 11 is prepared. In the base material preparation step S1, a base material 11 made of any of the above-mentioned materials is prepared.
[0028] In the film formation step S2, the ScAlN film 12 is formed on the surface of the base material 11. In the film formation step S2, the base material 11 is placed in a film formation device, and the ScAlN film 12 is formed at a predetermined film formation temperature by a reactive sputtering method. After the ScAlN film 12 is formed and before annealing, the unpaired electron density of the ScAlN film 12 is 1.1×10 19 (pcs / cm 3 ) is greater than
[0029] In the annealing step S3, the ScAlN film 12 is annealed. In the annealing step S3, the ScAlN film 12 is heated at an annealing temperature higher than the film formation temperature. This reduces the unpaired electron density of the ScAlN film 12 compared to before the annealing. Specifically, the unpaired electron density of the ScAlN film 12 is reduced to 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 ) or less. As described later, the annealing temperature for achieving such a magnitude of unpaired electron density can be a temperature 30° C. or higher than the film formation temperature, or a temperature of 400° C. or higher. The annealing temperature may be any temperature lower than the melting points of the base material 11 and the ScAlN film 12.
[0030] As an example of the procedure of the annealing step S3, the piezoelectric film laminate 10 having the ScAlN film 12 formed on the surface of the base material 11 is moved from a film forming apparatus to the inside of an annealing apparatus. The piezoelectric film laminate 10 is then heated at a predetermined annealing temperature by the annealing apparatus. The piezoelectric film laminate 10 may be heated inside the film forming apparatus without being moved from the film forming apparatus to the annealing apparatus. In this case, after the ScAlN film 12 is formed, the heating temperature by the film forming apparatus is increased from the film forming temperature to the annealing temperature. However, the heating temperature by the film forming apparatus may be decreased below the film forming temperature and then increased to the annealing temperature.
[0031] The annealing atmosphere when annealing the ScAlN film 12 is desirably an atmosphere inert to ScAlN. Specifically, the annealing atmosphere is desirably an inert gas atmosphere or a vacuum state. Examples of the inert gas include nitrogen, argon, hydrogen, or a mixture of these gases.
[0032] Here, Table 1 shows the measurement results of the electron spin density and tan δ of the piezoelectric film laminate 10 of Samples 1 to 10 manufactured by the present inventors. Samples 1 to 10 correspond to sample numbers 1 to 10 in Table 1.
[0033] [Table 1]
[0034] Samples 4 to 10 are examples manufactured by the manufacturing method of this embodiment described above. Sample 1 is a comparative example manufactured by a manufacturing method in which the annealing step S3 is omitted from the manufacturing method of this embodiment described above. Samples 2 and 3 are comparative examples manufactured by a manufacturing method in which the conditions of the annealing step S3 are different from those of the manufacturing method of this embodiment described above. The electron spin density was measured by the measurement method described in this embodiment. Tan δ is a value at 1 kHz.
[0035] In the manufacturing of the piezoelectric film laminates 10 of Samples 1 to 10, in the film formation step S2, the inventors performed plasma discharge using a reactive sputtering device to form the ScAlN film 12 on the surface of a Si substrate serving as the base material 11. The film formation conditions for the ScAlN film 12 at this time are as follows. The Si substrate temperature is the film formation temperature when the ScAlN film 12 is formed.
[0036] Target type: ScAl target Target size: diameter 100mm Distance between Si substrate and target: 200 mm DC Power: 800W Pulse frequency: 20kHz Pulse length: 4μs Gas flow rate N 2 :28sccm, Ar:28sccm Gas pressure: 0.2Pa Si substrate temperature: 370℃ Resistivity of Si substrate: ≧1×10 3 Ω cm
[0037] The Sc concentration of the ScAl target used for depositing the ScAlN film 12 was 40 atomic %. The Sc concentration of the deposited ScAlN film 12 was 30 atomic %.
[0038] In sample 1, the ScAlN film 12 was not annealed. In samples 2 and 3, the ScAlN film 12 was annealed at 380° C. In samples 4 to 10, the ScAlN film 12 was annealed at each of the annealing temperatures shown in Table 1, which are 400° C. or higher.
[0039] In the annealing step S3, the inventors used a quartz tube furnace as the annealing device. The sample was placed in the annealing device, which was in a standby state of 200° C. Then, the internal temperature of the annealing device was raised to a preset temperature that was set so that the temperatures of the Si substrate and the ScAlN film 12 would be the respective annealing temperatures, and this temperature was maintained for 60 minutes. Then, the internal temperature of the annealing device was lowered to 200° C., and the sample was removed. When annealing, N was used as the atmospheric gas inside the annealing device. 2 The internal pressure of the annealing apparatus was set to 80 kPa.
[0040] Fig. 3 is a graph showing the relationship between tan δ and the electron spin density (i.e., unpaired electron density) of the ScAlN film 12 in Samples 1 to 10 in Table 1. As shown in Fig. 3, there is a relationship between tan δ and the unpaired electron density such that the higher the unpaired electron density, the larger tan δ becomes.
[0041] More specifically, the unpaired electron density of sample 4 is 1.1×10 19 (pcs / cm 3) is the boundary, and the rate of change in tan δ is different. The rate of change in tan δ is the rate of increase in tan δ to the increase in unpaired electron density. When the unpaired electron density of samples 4 to 10 is 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 The rate of change in tan δ in the range below is 1.1×10 for unpaired electron densities of samples 1 to 3. 19 (pcs / cm 3 ) is smaller than the rate of change in tan δ in a range larger than
[0042] That is, the unpaired electron density of samples 4 to 10 is 1.7 × 10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 ) or less, tan δ is 0.001 or less. In contrast, the unpaired electron density of samples 1 to 3 is 1.1 × 10 19 (pcs / cm 3 ), tan δ is greater than 0.001, and as the unpaired electron density increases, tan δ increases rapidly.
[0043] As shown in Table 1, the annealing temperatures of Samples 4 to 10 are not less than 400° C. and not more than 800° C. Fig. 4 is a graph showing the relationship between tan δ of the ScAlN film 12 and the annealing temperature for Samples 1 to 10 in Table 1. As shown in Fig. 4, when the annealing temperatures of Samples 4 to 10 are in the range of not less than 400° C. and not more than 800° C., tan δ is not more than 0.001.
[0044] Thus, the present inventors have found that the dominant factor in tan δ of the ScAlN film 12 is the unpaired electron density of the ScAlN film 12. The dominant factor in tan δ of the ScAlN film 12 is the leakage current, and the dominant factor in the leakage current is believed to be defects in the film, particularly dangling bonds. For this reason, it is believed that the dangling bond density (i.e., the unpaired electron density) is the dominant factor in tan δ.
[0045] The unpaired electron density of the ScAlN film 12 is 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 ) or less, the inventors have found that tan δ can be kept low. Therefore, according to the piezoelectric film laminate 10 of this embodiment, the unpaired electron density of the ScAlN film 12 is 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 ) or less, the tan δ of the ScAlN film 12 can be kept low.
[0046] Incidentally, the following documents disclose that the tan δ of an ScAlN film having an Sc concentration of 30 atomic % or more is higher than 0.001.
[0047] ·JOURNAL OF APPLIED PHYSICS 122, 035301 (2017) ·Proc. SPIE 9517, Smart Sensors, Actuators, and MEMS VII; and Cyber Physical Systems, 95171C (21 May 2015) ·APL MATERIALS 3, 116102 (2015) ·APPLIED PHYSICS LETTERS 97, 112902 2010
[0048] In contrast, according to the piezoelectric film laminate 10 of this embodiment, when the Sc concentration of the ScAlN film 12 is 30 atomic % or more and 45 atomic % or less, the tan δ of the ScAlN film 12 can be made 0.001 or less.
[0049] The method for manufacturing the piezoelectric film laminate 10 of this embodiment includes a base material preparation step S1, a film formation step S2, and an annealing step S3. In the annealing step S3, the ScAlN film 12 is heated at an annealing temperature higher than the film formation temperature when the ScAlN film 12 is formed, thereby reducing the unpaired electron density of the ScAlN film 12 to 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 According to this, the unpaired electron density of the ScAlN film 12 is set to 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 ) or less, it is possible to manufacture the piezoelectric film laminate 10 in which the tan δ of the ScAlN film 12 is kept low.
[0050] Here, when ScAlN is a single crystal without grain boundaries and the single crystal is free of crystal defects, there are no unpaired electrons in ScAlN. In contrast, when ScAlN is a polycrystal with grain boundaries or when ScAlN has crystal defects, there are unpaired electrons in ScAlN. In other words, when there are crystal imperfections in ScAlN, unpaired electrons appear. By annealing the ScAlN film, the crystal imperfections of ScAlN are repaired and the unpaired electrons are reduced. For this reason, it is believed that the unpaired electron density of ScAlN film 12 is reduced by annealing.
[0051] As shown in Table 1, the unpaired electron density of samples 1 to 10 was 1.1 × 10 19 (pcs / cm 3 ) or less in Samples 4 to 10. The annealing temperature in Samples 4 to 10 is 400° C. or more. Therefore, when the unpaired electron density of the ScAlN film 12 is 1.1×10 19 (pcs / cm 3 ) or less, it is believed that an annealing temperature of 400° C. or higher in the annealing step S3 is effective.
[0052] Moreover, the annealing temperatures of Samples 4 to 10 are higher than the film formation temperatures by 30° C. or more. From another point of view, therefore, the unpaired electron density of the ScAlN film 12 is 1.1×10 19 (pcs / cm 3 ) or less, it is believed to be effective for the annealing temperature in the annealing step S3 to be 30° C. or more higher than the film formation temperature.
[0053] Second embodiment 5 uses the piezoelectric film laminate 10 of the first embodiment. The microphone 20 includes a pressure receiving portion 21 and a support 22. The pressure receiving portion 21 is a membrane-like portion that receives sound pressure. The support 22 supports the pressure receiving portion 21.
[0054] The support 22 has a space 23 for the pressure-receiving portion 21 to deform when subjected to sound pressure. The support 22 supports the pressure-receiving portion 21 with the pressure-receiving portion 21 positioned above the space 23 so that the pressure-receiving portion 21 can deform when subjected to sound pressure. The support 22 is made of Si.
[0055] The pressure-receiving portion 21 includes a piezoelectric film 24, a lower electrode 25, an upper electrode 26, and an insulating film 27. The piezoelectric film 24 is the same film as the ScAlN film 12 of the first embodiment. The lower electrode 25 is formed in contact with the lower surface of the piezoelectric film 24. The upper electrode 26 is formed in contact with the upper surface of the piezoelectric film 24. The lower electrode 25 and the upper electrode 26 are electrodes for recovering electric charges generated in the piezoelectric film 24 due to deformation of the pressure-receiving portion 21. The lower electrode 25 and the upper electrode 26 are made of Mo. The insulating film 27 covers the space portion 23 and the area surrounding the space portion 23 of the support 22. The insulating film 27 is a Si oxide film.
[0056] The lower electrode 25 is provided on the surface of a region of the insulating film 27 located above the space 23. The piezoelectric film 24 is formed over the upper surface of the lower electrode 25 and the surface of the insulating film 27 on which the lower electrode 25 is not formed. Therefore, the lower electrode 25 and the insulating film 27 correspond to the base material 11 of the first embodiment.
[0057] In the microphone 20 configured in this manner, the pressure receiving portion 21 is deflected and deformed when subjected to sound pressure. When the pressure receiving portion 21 is deformed into a downward convex shape, a compressive stress is generated in the in-plane direction of the piezoelectric film 24. At this time, charges are generated on the surface of the piezoelectric film 24 due to the piezoelectric effect. Also, when the pressure receiving portion 21 is deformed into an upward convex shape, a tensile stress is generated in the in-plane direction of the piezoelectric film 24. At this time, charges of the opposite polarity to when compressive stress is generated are generated on the surface of the piezoelectric film 24 due to the piezoelectric effect. Therefore, by collecting the generated charges through the lower electrode 25 and the upper electrode 26, the sound pressure applied to the pressure receiving portion 21 can be detected.
[0058] According to this embodiment, the ScAlN film 12 of the first embodiment is used as the piezoelectric film 24. As explained in the first embodiment, the tan δ of the ScAlN film 12 is kept low. When comparing the contribution of each factor to microphone noise, it is known that the contribution of tan δ is the largest in the entire frequency range used by the microphone. Therefore, the noise of the microphone 20 can be reduced.
[0059] In this embodiment, the insulating film 27 is included in the pressure receiving portion 21. However, the insulating film 27 may be a conductive film other than the lower electrode 25. In this embodiment, the insulating film 27 is formed so that the neutral line in the bending deformation of the pressure receiving portion 21 does not exist in the piezoelectric film 24. When the neutral line in the bending deformation of the pressure receiving portion 21 does not exist in the piezoelectric film 24 by making the lower electrode 25 thicker than the upper electrode 26, for example, the insulating film 27 may not be included in the pressure receiving portion 21. In this embodiment, the piezoelectric film 24, the lower electrode 25, and the upper electrode 26 have shapes shown in FIG. 5. However, these shapes are not limited to the shapes shown in FIG. 5. In addition, each of the lower electrode 25, the upper electrode 26, the support 22, and the insulating film 27 may be made of a material other than the above-mentioned materials.
[0060] Third embodiment 6 is a BAW device using the piezoelectric film laminate 10 of the first embodiment. BAW is an abbreviation for Bulk Acoustic Wave. The BAW resonator 30 includes a piezoelectric film 31, a lower electrode 32, an upper electrode 33, and a support 34.
[0061] The piezoelectric film 31 is the same film as the ScAlN film 12 of the first embodiment. The lower electrode 32 is formed in contact with the lower surface of the piezoelectric film 31. The upper electrode 33 is formed in contact with the upper surface of the piezoelectric film 31. The lower electrode 32 and the upper electrode 33 are electrodes that apply an AC electric field to the piezoelectric film 31 to vibrate the piezoelectric film 31 in the film thickness direction. The lower electrode 32 and the upper electrode 33 are made of Mo.
[0062] The support 34 supports the piezoelectric film 31, the lower electrode 32, and the upper electrode 33. The support 34 has a space 35 for the piezoelectric film 31 to vibrate when an AC electric field is applied to the piezoelectric film 31. The support 34 is made of Si. The lower electrode 32 faces the space 35 of the support 34. In this embodiment, the piezoelectric film 31 is formed on the surface of the lower electrode 32 and on the surface of the support 34. Therefore, the lower electrode 32 and the support 34 correspond to the base material 11 of the first embodiment.
[0063] In the BAW resonator 30 configured in this manner, when a voltage is applied between the upper electrode 33 and the lower electrode 32, the piezoelectric film 31 expands and contracts in the film thickness direction indicated by the arrow in FIG. 6 due to the inverse piezoelectric effect. When a sinusoidal voltage waveform is applied, this expansion and contraction vibration also has a sinusoidal vibration waveform. When this frequency coincides with the resonant frequency of the mechanical vibration, the impedance between the upper electrode 33 and the lower electrode 32 changes significantly. This makes the BAW resonator 30 of this embodiment an electrical resonator. By using a plurality of such resonators and connecting them in a circuit, a filter operation is possible.
[0064] According to this embodiment, the ScAlN film 12 of the first embodiment is used as the piezoelectric film 31. As described in the first embodiment, the tan δ of the ScAlN film 12 is kept low. This makes it possible to increase the Q value of the resonator. This makes it possible to improve the filter characteristics of the BAW resonator 30.
[0065] In the BAW resonator 30 of this embodiment, the support 34 has a space 35. However, the support 34 does not have to have the space 35. In this case, the BAW resonator 30 only needs to include an acoustic multilayer film between the lower electrode 32 and the support 34. Furthermore, each of the lower electrode 32, the upper electrode 33, and the support 34 may be made of a material other than the above-mentioned materials.
[0066] (Fourth embodiment) 7 uses the piezoelectric film laminate 10 of the first embodiment. SAW is an abbreviation for Surface Acoustic Wave.
[0067] The SAW device 40 includes a substrate 41, a piezoelectric film 42, and a comb-tooth electrode 43. The substrate 41 is made of Si. The substrate 41 corresponds to the base material 11 of the first embodiment. The piezoelectric film 42 is the same film as the ScAlN film 12 of the first embodiment. The piezoelectric film 42 is provided on the surface of the substrate 41. The comb-tooth electrode 43 is provided on the surface of the piezoelectric film 42. The comb-tooth electrode 43 excites a SAW in the piezoelectric film 42, or receives a SAW propagating through the piezoelectric film 42. The comb-tooth electrode 43 is made of Mo. The SAW device 40 includes a SAW resonator, a SAW filter, and the like.
[0068] Although not shown, an example of a SAW resonator is a one-port type SAW resonator. In this SAW resonator, reflectors are arranged on both sides of the comb-tooth electrode 43 on the surface of the piezoelectric film 42. In this SAW resonator, a SAW excited by the comb-tooth electrode 43 is reflected by both reflectors, generating a standing wave. This realizes a resonator. According to this embodiment, the ScAlN film 12 of the first embodiment is used as the piezoelectric film 42. As explained in the first embodiment, the tan δ of the ScAlN film 12 is kept low. This makes it possible to increase the Q value of the SAW resonator. This makes it possible to improve the filter characteristics of the SAW resonator.
[0069] Although not shown, another example of a SAW device is a transversal SAW filter. In this SAW filter, the comb-tooth electrode 43 includes an input electrode and an output electrode. The SAW excited by the input electrode propagates along the surface of the piezoelectric film 42 and is detected by the output electrode. This makes it possible to extract an electrical signal in a specific frequency band. According to this embodiment, the ScAlN film 12 of the first embodiment is used as the piezoelectric film 42. As explained in the first embodiment, the tan δ of the ScAlN film 12 is kept low. This makes it possible to improve the filter characteristics of the SAW filter.
[0070] Each of the substrate 41 and the comb-tooth electrode 43 may be made of a material other than the above-mentioned materials.
[0071] Fifth embodiment 8 uses the piezoelectric film laminate 10 of the first embodiment. MEMS is an abbreviation for Micro Electro Mechanical Systems.
[0072] The MEMS resonator 50 includes a three-layer structure 51 and a support 52. The three-layer structure 51 includes a piezoelectric film 53, a lower electrode 54, and an upper electrode 55.
[0073] The piezoelectric film 53 is the same film as the ScAlN film 12 in the first embodiment. The lower electrode 54 is formed in contact with the lower surface of the piezoelectric film 53. The upper electrode 55 is formed in contact with the upper surface of the piezoelectric film 53. The lower electrode 54 and the upper electrode 55 are electrodes that apply an AC electric field to the piezoelectric film 53 to expand and contract the piezoelectric film 53 in the in-plane direction of the piezoelectric film 53. The lower electrode 54 and the upper electrode 55 are made of Mo. In this embodiment, the piezoelectric film 53 is formed on the surface of the lower electrode 54. Therefore, the lower electrode 54 corresponds to the base material 11 in the first embodiment.
[0074] The support 52 has a space 56. The support 52 supports the three-layer structure 51 in a state in which the three-layer structure 51 can vibrate above the space 56. In this embodiment, a cantilever structure is formed in which one end of the three-layer structure 51 in one direction is fixed to the support 52 and the other end of the three-layer structure 51 in one direction is free. The support 52 includes a substrate 57 and an insulating film 58. The substrate 57 is made of Si. The insulating film 58 is formed on the surface of the substrate 57. The insulating film 58 is a Si oxide film. The lower electrode 54 is formed on the surface of the insulating film 58.
[0075] The thickness of the lower electrode 54 is equal to or greater than the total thickness of the upper electrode 55 and the piezoelectric film 53. Therefore, the neutral line in the flexural deformation of the three-layer structure 51 is inside the lower electrode 54. When a voltage is applied between the upper electrode 55 and the lower electrode 54, the piezoelectric film 53 expands and contracts in the in-plane direction of the film due to the inverse piezoelectric effect. Then, the entire three-layer structure 51 flexes. When a sinusoidal voltage waveform is applied, this flexural deformation also becomes a sinusoidal vibration. When the frequency coincides with the resonant frequency of the flexural vibration, the impedance between the upper electrode 55 and the lower electrode 54 changes significantly. This makes it an electrical resonator. Using this resonator, a reference frequency required for the operation of an arithmetic circuit or the like can be generated.
[0076] According to this embodiment, the ScAlN film 12 of the first embodiment is used as the piezoelectric film 53. As described in the first embodiment, the tan δ of the ScAlN film 12 is kept low. This makes it possible to increase the Q value of the resonator. This makes it possible to increase the accuracy of the generated reference frequency.
[0077] The lower electrode 54, the upper electrode 55, the substrate 57, and the insulating film 58 may each be made of a material other than the above-mentioned materials. If the substrate 57 is an insulator, the insulating film 58 does not need to be formed.
[0078] (Other embodiments) (1) In the first embodiment, in the method for manufacturing the piezoelectric film laminate 10, the annealing step S3 is performed after the film formation step S2, thereby reducing the unpaired electron density of the ScAlN film 12 to 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 However, without performing the annealing step S3, the unpaired electron density of the ScAlN film 12 after film formation is set to 1.7×10 18 (pcs / cm 3 ) or more, 1.1×10 19 (pcs / cm 3 ) or less, the annealing step S3 may not be performed.
[0079] (2) The present invention is not limited to the above-described embodiment, and can be appropriately modified within the scope of the claims, and includes various modified examples and modifications within the equivalent scope. The above-described embodiments are not unrelated to each other, and can be appropriately combined, except when the combination is clearly impossible. In the above-described embodiments, it goes without saying that the elements constituting the embodiments are not necessarily essential, except when they are specifically stated to be essential or when they are clearly considered to be essential in principle. In the above-described embodiments, when the numbers, values, amounts, ranges, etc. of the components of the embodiments are mentioned, they are not limited to the specific numbers, except when they are specifically stated to be essential or when they are clearly limited to a specific number in principle. In the above-described embodiments, when the materials, shapes, positional relationships, etc. of the components are mentioned, they are not limited to the materials, shapes, positional relationships, etc., except when they are specifically stated to be essential or when they are clearly limited to a specific material, shape, positional relationship, etc. in principle. [Explanation of symbols]
[0080] 10 Piezoelectric film laminate 11 Base material 12 ScAlN membrane
Claims
1. A piezoelectric film laminate, Base materials (11, 25, 27, 32, 34, 41, 54), A ScAlN film (12, 24, 31, 42, 53) formed on the surface of the base material; Equipped with The unpaired electron density of the ScAlN film is 8.0×10 18 (electrons / cm 3 ) or more, and 1.1×10 19 (pcs / cm 3 ) or less.
2. A piezoelectric film laminate, Base materials (11, 25, 27, 32, 34, 41, 54), A ScAlN film (12, 24, 31, 42, 53) formed on the surface of the base material; Equipped with The ScAlN film has an unpaired electron density of 8.0×10 18 (electrons / cm 3 ) or more and 1.1×10 19 (electrons / cm 3 ) or less, and the tan δ of the ScAlN film is 8.1×10 -4 That's it, 1.0 x 10 -3 The piezoelectric film laminate is as follows:
3. The piezoelectric film laminate of claim 1 or 2, wherein in the ScAlN film, the Sc concentration, which is the ratio of the number of Sc atoms to the total number of Sc atoms and Al atoms (100 atomic %), is 30 atomic % or more and 45 atomic % or less.
4. A method for manufacturing a piezoelectric film laminate, comprising the steps of: Preparing a base material (11) (S1); forming a ScAlN film (12) on the surface of the base material (S2); and adjusting the unpaired electron density of the ScAlN film by annealing (S3). In the adjustment of the unpaired electron density, the unpaired electron density of the ScAlN film is adjusted to 8.0×10 18 (electrons / cm 3 ) or more, and 1.1×10 19 (pcs / cm 3 ) 1. A method for producing a piezoelectric film laminate.
5. 5. The method for producing a piezoelectric film laminate according to claim 4, wherein adjusting the unpaired electron density includes an annealing step of annealing the ScAlN film at an annealing temperature higher than a film-forming temperature when the ScAlN film is formed.
6. The method for producing a piezoelectric film laminate according to claim 5 , wherein the annealing temperature is at least 30° C. higher than the film formation temperature.
7. The method for producing a piezoelectric film laminate according to claim 5 or 6, wherein the annealing temperature is 400° C. or more and 475° C. or less.
8. The annealing step is carried out using N 2 The method for producing a piezoelectric film laminate according to any one of claims 5 to 7, further comprising heating the ScAlN film in an atmosphere.
9. The method for producing a piezoelectric film laminate according to any one of claims 5 to 8, wherein the annealing step includes heating the ScAlN film under a reduced pressure.
10. The method for producing a piezoelectric film laminate according to claim 9 , wherein the reduced pressure state is a vacuum state.
11. The method for producing a piezoelectric film laminate according to any one of claims 5 to 10, wherein the annealing step is carried out inside an annealing device.
Citation Information
Patent Citations
Method for manufacturing thin aluminum nitride film utilizing plasma treatment
JP2001253778A
Method of manufacturing piezoelectric thin film, and piezoelectric thin film manufactured by the method
JP2011015148A
JP2019-1456677A
Method for manufacturing piezoelectric device
WO2016114172A1